Cytokeratin 17 expression is commonly observed in keratinocytic skin tumours and controls tissue homeostasis impacting human papillomavirus protein expression - Hasche, Daniel; Hufbauer, Martin; Braspenning-Wesch, Ilona; Stephan, Sonja; Silling, Steffi; Schmidt, Gabriele; Krieg, Stephan; Kreuter, Alexander; Akgül, Baki (British journal of dermatology, 2024)
The structured expression of several keratins in the skin is associated with differentiation status of the epidermal layers, whereas other keratins are upregulated only during wound healing, in skin disorders and in cancers. One of these stress keratins, K17, is correlated with poor prognosis in various cancer types and its loss has been shown to decelerate tumour growth. K17 expression can also be detected in cutaneous squamous cell carcinomas, where ultraviolet irradiation and infection with cutaneous human papillomaviruses are important cofactors. It was previously reported that K17 is upregulated in papillomavirus (PV)-induced benign skin lesions in mice and induces an immunological status that is beneficial for tumour growth.In order to investigate whether K17 upregulation is induced by PVs, we analysed K17 levels in skin tumour specimens of different animal models and humans.Various immunofluorescence stainings were performed to identify K17 expression as well as levels of E-cadherin, vimentin and CD271. Tissues were further analysed by polymerase chain reaction (PCR), quantitative (q)PCR and enzyme-linked immunosorbent assay to control for PV activity. K17 knockdown cells were generated and effects on viral life cycle were investigated by infection assays, qPCR and Western blotting.We showed that K17 is commonly expressed in skin tumours and that its presence is not directly linked to viral oncoprotein expression. Rather, K17 expression seems to be a marker of epithelial differentiation and its absence in tumour tissue is associated with an epithelial-to-mesenchymal transition. We further demonstrated that the absence of K17 in skin tumours increases markers of cancer stem-like cells and negatively affects viral protein synthesis.Collectively, our data indicate that K17 expression is a common feature in skin tumorigenesis. While K17 is not primarily targeted by PV oncoproteins, our in vivo and in vitro data suggest that it is an important regulator of epithelial differentiation and thus may play a role in controlling viral protein synthesis.